Letter from the Editor - Makinde, Peter Oyewole (WritingThreeSixty, 2024)
Dear readers, I present the first issue of WritingThreeSixty for 2024. It has been exciting work as the newly appointed Editor-in-Chief working alongside the new Editorial Board and producing this issue since the journal's hiatus after the previous issue as a result of the Covid pandemic. The Editorial Board of WritingThreeSixty were overwhelmed by the support from our readers and the writers who have previously published their works in this journal which made this relaunch successful. The new Editorial Board has put together a collection of articles that respond to the theme of this issue, namely, the influence of Artificial Intelligence (AI) in transforming the world of academia, scholarship, and the arts. Responses to the call for papers for the AI Special Issue interestingly show that most writers chose poetry as the medium used to respond to the theme for this issue. This issue also features other creative works and academic articles from talented writers across Africa. I hope you find it a pleasure to read the AI Special Issue Volume 7 Issue 1 and to participate in the conversation WritingThreeSixty is having with African creators, academics, and audiences abroad on the current issue.